Fluidization, solids handling, and processing : industrial applications - Yang, Wen-ching, 1939- (Noyes Publications, 1998)
Particles are important products of chemical process industries spanning the basic and specialty chemicals, agricultural products, pharmaceuticals, paints, dyestuffs and pigments, cement, ceramics, and electronic materials. Solids handling and processing technologies are thus essential to the operation and competitiveness of these industries. Fluidization technology is employed not only in chemical production, it also is applied in coal gasification and combustion for power generation, mineral processing, food processing, soil washing and other related waste treatment, environmental remediation, and resource recovery processes. The FCC (Fluid Catalytic Cracking) technology commonly employed in the modern petroleum refineries is also based on fluidization principles.
Keywords: Fluidization.; Bulk solids flow.; elektronické knihy; electronic books